Interdisciplinary Approach to Spationtemporal Population Dynamics. The North Orkney Population History Project - Julia A. Jennings; Corey S. Sparks; Timothy Murtha (Historical Life Course Studies)
The North Orkney Population History Project is a multidisciplinary data collection, digitization, and analysis effort that aims to reconstruct longitudinal demographic, environmental, and economic change. We describe the motivation, methodological approach, data sources, and some initial findings of the project. Detailed contextual information about a single community allows for the joint analysis of the changing population and changing landscape. The combination of diverse data sources and disciplinary approaches has resulted in findings that would not have been possible if each source had been considered in isolation. The approach adopted by the project offers a way to examine the interaction of a population with its landscape over a period of change.